A randomised controlled crossover trial of nurse practitioner versus doctor led outpatient care in a bronchiectasis clinic. Issue 8 (1st August 2002) - Sharples, L D; Edmunds, J; Bilton, D; Hollingworth, W; Caine, N; Keogan, M; Exley, A
Abstract : Background: With the decrease in junior doctor hours, the advent of specialist registrars, and the availability of highly trained and experienced nursing personnel, the service needs of patients with chronic respiratory diseases attending routine outpatient clinics may be better provided by appropriately trained nurse practitioners. Methods: A randomised controlled crossover trial was used to compare nurse practitioner led care with doctor led care in a bronchiectasis outpatient clinic. Eighty patients were recruited and randomised to receive 1 year of nurse led care and 1 year of doctor led care in random order. Patients were followed up for 2 years to ensure patient safety and acceptability and to assess differences in lung function. Outcome measures were forced expiratory volume in 1 second (FEV1 ), 12 minute walk test, health related quality of life, and resource use. Results: The mean difference in FEV1 was 0.2% predicted (95% confidence interval –1.6 to 2.0%, p=0.83). There were no significant differences in the other clinical or health related quality of life measures. Nurse led care resulted in significantly increased resource use compared with doctor led care (mean difference £1497, 95% confidence interval £688 to £2674, p<0.001), a large part of which resulted from the number and duration of hospital admissions. The mean difference in resource use was greater in the first year (£2625) than in the second year (£411). Conclusions: Nurse practitioner led care for stable patients within a chronic chest clinic is safe and is as effective as doctor led care, but may use more resources.